Информационно-компьютерные технологии в изучении философских дисциплин: возможности и проблемы - Штанько, В. И. (УАДО, 2004)
lnformatively-computer technologies (1CT) are actively inculcated in the sphere of education. Their application in the process of study of philosophical disciplines in an institute is attended with some problems conditioned by the specific of philosophical knowledge. Possibilities of creation of electronic textbook in philosophy, problems, arising up at development of test tasks of knowledge control in philosophical disciplines and using of the resources of the Internet are examined in the report.
Keywords: изучение философских дисциплин